Coming to America: Assessing the Patterns of Acculturation, Friendship Formation, and the Academic Experiences of International Students at a U.S. College - Leong, Pamela (Journal of International Students, 2015)
Using interview data from 11 international students, this paper compares international students’ experiences at a single American university, and the acculturation issues that they encountered. The students assessed their experiences at the university, both positive and negative, and discussed their perceptions of American ways of doing things. The findings suggest that, when compared to students from other countries, students from China face considerable more difficulties both academically and socially, given the formidable language and cultural barriers. These challenges remain regardless of whether the students self-segregate with co-nationals or associate primarily with Americans. While individual-level factors (e.g., language fluency and coping ability) affect the international students’ lived experiences and perceived satisfaction level while studying in the United States, this paper argues that environmental factors (e.g., the culture and reception of the host society) may be more important in shaping the experiences of international students, whether for better or worse.